Evaluasi Capability Level Tata Kelola TI Berbasis COBIT 2019 untuk Mendukung Transformasi Digital Perguruan Tinggi - Amalia, Rifka Dwi; Krisnanik, Erly; Kraugusteeliana (Jurnal Penelitian Teknologi Informasi dan Sains, 2026)
The increasing role of information technology in higher education requires IT governance practices that are measurable, structured, and aligned with digital transformation objectives. Many higher education institutions have implemented various information systems to support academic, administrative, and managerial services; however, the existence of technology does not automatically ensure that IT processes are governed effectively. This study aims to evaluate the Capability level of IT governance using the COBIT 2019 framework in the context of a state university in Indonesia. A descriptive case study approach was applied through structured interviews, document analysis, and observation of IT governance practices. The evaluation focused on eleven Governance and Management Objectives across the EDM, APO, BAI, DSS, and MEA domains. The results show that most objectives are at Capability Level 1 (Performed), while only BAI01, BAI03, and DSS02 have reached Capability Level 2 (Managed). No evaluated objective has reached Level 3 (Established). The gap analysis indicates that the highest gaps are found in EDM03, APO12, and APO13, which relate to risk optimization, risk management, and security governance. These findings indicate that IT governance practices have been implemented but still require stronger formal policies, standardized procedures, documented controls, and integrated monitoring mechanisms. The study provides practical recommendations for improving IT governance through risk appetite definition, risk register development, information security policy, enterprise architecture blueprint, service level agreement implementation, and performance monitoring to support sustainable digital transformation in higher education.